Menakar Model Pemakzulan Kepala Daerah di Era Orde Lama dan Kaitannya dengan Karakter Negara Kesatuan - La Ode Muhaimin (Faculty of Law Hang Tuah University, 2021)
The design of impeachment for a regional head in the Old Order era has similarities in terms of assigning authority to the central government and having a single model. However, it differs in terms of giving roles to the Regional People's Representative Council (DPRD). The difference in the aspect of DPRD involvement is linear with the procedure for filling the position of Regional Head. This study aims to describe the impeachment pattern of Regional Heads in the Old Order era in the perspective of a unitary state and to find the relationship between the impeachment patterns of Regional Heads with the Government's objective of cementing central and regional relations. This research is a normative and literary legal research conducted by examining library materials or secondary data. The material of this research is primary legal materials, namely laws and regulations concerning the impeachment of regional heads issued during the Old Order period. The impeachment pattern of regional heads in the Old Order era experienced a shift, from a decentralized pattern to a centralized pattern after entering the Guided Democracy era. The design of impeachment with a centralized pattern and continued until the end of President Soekarno's rule. The pattern of impeachment which was characterized by centralization during the Old Order era was one of the factors causing the impeachment pattern of Regional Heads to rest in the hands of the Central Government.